Does Learning Behavior Moderate the Influence of Emotional Intelligence and Spiritual Intelligence on Vocational Accounting Students? - Yuli Anastasya Br Sinuhaji; Andri Zainal; Jufri Darma; Rini Herliani; Choms Gary Ganda Tua Sibarani (Universitas Muhammadiyah Surakarta, 2024)
Inadequate comprehension of accounting among students in class X who specialize in accounting at a vocational school in Medan is the primary concern of this investigation. The objective of this investigation is to ascertain the influence of emotional intelligence on the understanding of accounting. (2). The influence of spiritual intelligence on the understanding of accountancy. (3). The influence of spiritual intelligence and emotional intelligence on the understanding of accountancy. (4). Is the relationship between emotional intelligence and accounting comprehension moderated by learning behavior? (5). Is the relationship between spiritual intelligence and accounting comprehension moderated by learning behavior? This investigation is retrospective. The population for this study consisted of all 140 students enrolled in the Vocational Accounting program in class X. The research included a sample of 140 students, and the sampling approach used was complete sampling. The information was gathered using research interviews and accounting exam queries. The research questionnaire underwent initial testing to assess its validity and reliability. However, the accounting comprehension test questions were not subjected to such testing as they were derived from a multiple-choice test found in a school textbook with a legitimate ISBN. Subsequently, the data underwent processing utilizing the SPSS version 25 software. The research findings indicated that Emotional Intelligence and Spiritual Intelligence had a favorable and substantial impact on Accounting Understanding, with the influence being controlled by Learning Behaviour.